2018
DOI: 10.3892/ijo.2018.4428
|View full text |Cite
|
Sign up to set email alerts
|

[Corrigendum] Long non‑coding RNA�H19 promotes cell proliferation and invasion by acting as a ceRNA of miR‑138 and releasing EZH2 in oral squamous cell carcinoma

Abstract: Following the publication of this article, we realize that the title appeared incorrectly: This appeared in print as "Long non-coding RNA H1 promotes cell proliferation and invasion by acting as a ceRNA of miR-138 and releasing EZH2 in oral squamous cell carcinoma", and the corrected title is now featured above ("H1" should have read as "H19").Note that this error did not have any bearing on the results reported in the paper, or on the conclusions therein. We regret any inconvenience that this mistake has caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although a similar relationship between H19 and Id2 has been indicated previously in bladder cancer cells and acute myelocytic leukemia cells, the underlying mechanistic relationship between them have not been well investigated [17, 18]. Inspired by the newly reported regulatory mechanism that H19 functioned as a competing endogenous RNA (ceRNA) via sponging miRNA [1921, 2830], we employed bioinformatics analysis to predict that H19 promoted Id2 expression via acting as a ceRNA by sponging miR-19a. With dual luciferase reported assay, RIP and pull-down experiments, we demonstrated the dual competitive interaction of miR-19a with H19 and the 3′-UTR of Id2 mRNA.…”
Section: Discussionmentioning
confidence: 91%
“…Although a similar relationship between H19 and Id2 has been indicated previously in bladder cancer cells and acute myelocytic leukemia cells, the underlying mechanistic relationship between them have not been well investigated [17, 18]. Inspired by the newly reported regulatory mechanism that H19 functioned as a competing endogenous RNA (ceRNA) via sponging miRNA [1921, 2830], we employed bioinformatics analysis to predict that H19 promoted Id2 expression via acting as a ceRNA by sponging miR-19a. With dual luciferase reported assay, RIP and pull-down experiments, we demonstrated the dual competitive interaction of miR-19a with H19 and the 3′-UTR of Id2 mRNA.…”
Section: Discussionmentioning
confidence: 91%
“…Accumulating evidences indicated that lncRNAs exerted the function by interacting with miRNAs . Therefore, to uncover potential target miRNAs of MEG3, the bioinformatics prediction analysis was performed by miRDB online website.…”
Section: Resultsmentioning
confidence: 99%
“…EZH2 is regulated by H19, through sponging of miR-630 (Li et al, 2016). Additionally, and through sponging miR-130, it was reported that H19 regulate EZH2 expression (Hong et al 2018). The functional outputs of H19-EZH2 association have been reported in a number of studies and using di erent models.…”
Section: H19 Lncrna Epigenetically Modulate Gene Expressionmentioning
confidence: 99%